Relationship of Patient knowledge with diabetes wound treatment measures in Dendang Village, Stabat District Langkat Regency - Panjaitan, Nurhikmah; Aswat, Ponidi (Jurnal Kesehatan Langkat Berseri (JURKESLASER), 2021)
Patients with Diabetes Mellitus (DM) are at risk for complications if not handled properly, one of the complications that often occurs is wounds on the feet which eventually become Diabetic Ulcers. One of the preventions for diabetic ulcers is regular foot care that will effectively prevent diabetic ulcers. Good knowledge about diabetes disease and wound care is needed for the implementation of diabetic wound care in patients in Dendang Village, Stabat District, Langkat Regency.The purpose of this study was to determine the relationship between the patient's level of knowledge with diabetes mellitus wound care measures in Dendang Village, Stabat District, Langkat Regency. 2020. This type of research is a correlation description using a cross sectional research design, the number of samples is 89 respondents. The results of this study showed 22 respondents (24.7%) with good knowledge, 41 respondents (46.1%) with sufficient knowledge and 26 respondents (29.2%) with less knowledge. Based on diabetes wound care, 43 respondents (48.3%) took good care of wounds, and 46 respondents (51.7%) did not treat wounds properly. The conclusion of the study is that there is a relationship between the level of patient knowledge and the action of diabetic wound care, which is significant P Value is 0.000, df is equal to 2, where sig < 0.000 <0.05, it is expected that puskesmas nurses will provide motivation to patients and families to improve foot care. Diabetic patients in the family by involving diabetic patients participate in foot care education activities at the puskesmas in healing diabetic wounds.